Socio-Demographic and Programmatic Determinants of Obstetric Morbidity and Related Care Seeking Behaviour in Nepal - Sharma, Sharad Kumar; Subedi, Bal Krishna; Adhikari, Dadhi (Economic Journal of Nepal, 2008)
Maternal mortality and morbidity is used as a key indicator for the monitoring of maternal health in international literature. Care seeking patterns in terms of obstetric morbidity in Nepalese context is scanty. The objective of this study is to examine if there is variation of obstetric morbidity and care seeking behaviour across the clusters and to investigate the association of sociodemographic, programmatic and community factors with obstetric morbidity and related care seeking behaviour. The findings show that 21 perreru women reported having experienced obstetric morbidity during pregnancy and of them 65 percent sought care for the morbidity. Women living in mountain were more likely to report morbidity but less likely to seek care compared to those living in Terai. While age, education, alcohol consumption and exposure of radio program on maternal health were significant predictors of obstetric morbidity, age. education, receipt of iron tablet and smoking were significant predictor for care seeking behaviour. Both the obstetric morbidity and care seeking behaviour varied across the clusters, however, only a small portion of the cluster-level variation were explained by explanatory variables. Key words: Care seeking; Maternal health; Obsteric morbidity; Nepal Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 31, No. 4 October-December 2008, Issue No. 124 Page: 212-221 Uploaded date: 5 July 2011